Uneasy partnership the politics of business and government in Canada - Hale, Geoffrey E. 1955- (University of Toronto Press, 2018)
"The Canadian government's pursuit of economic growth is central to its economic policy and to the nature of its relationship with the business community. The government depends on business investment for economic growth vital to the prosperity of citizens, the generation of tax revenues, and enough public satisfaction to win re-election. Businesses depend on the government for stable sets of rules that are necessary for success. They often look to governments for protection against threats to their well-being and for assistance in competing with other businesses. In this new edition of Uneasy Partnership, Geoffrey Hale examines the interdependent relationship between Canadian governments and businesses, considering the political role of the government in the economy and what effect this has on the business environment. Hale provides an overview of the historical dimensions of Canada's political economy and relations between government and business, giving readers background to consider topics such as corporate power, the implications of Canada's economic structure, regional economic differences, and the role of interest groups in political and policy processes, among others. In a thoughtful and well-researched style, Hale lays out how the partnership between business and government in Canada is an uneasy one...and one whose capacity to adapt to ongoing changes is essential in an uncertain world."...